Hydropower Turbine Friction Monitoring Dataset - Sandström, Lars-Johan; Berglund, Kim; Marklund, Pär; Simmons, Gregory F. (Luleå University of Technology, 2025)
The datasets contain pressure and temperature signals from the hydraulic systems of two different Kaplan turbines. The variables can be connected to the forces required to regulate the runner blades on the turbines. The datasets can therefore be used to monitor the friction in the bearings that enable the movement of the runner blades. These bearings are located in the hub of the Kaplan turbines. The datasets are also labeled with information on whether glycerol is present in the systems for lubrication.

The sampling frequency is 1 sample per minute. Each feature includes an average, minimum, and maximum value, which correspond to the statistics during that minute from the sampling as the sampling frequency in the SCADA system is higher than 1 sample per minute.

Dataseten innehåller tryck- och temperatursignaler från de hydrauliska systemen i två olika Kaplan-turbiner. Variablerna kan kopplas till de krafter som krävs för att reglera löphjulsbladen på turbinerna. Dataseten kan därför användas för att övervaka friktionen i lagren som möjliggör rörelsen av löphjulsbladen. Dessa lager är placerade i navet på Kaplan-turbinerna. Dataseten är också märkta med information om när glycerol finns i systemen för smörjning.

Samplingsfrekvensen är 1 prov per minut. Varje variabel innehåller ett medel-, min- och maxvärde, vilka motsvarar statistiken under den minuten, eftersom samplingsfrekvensen i SCADA-systemet är högre än 1 prov per minut.
Hydropower Turbine Friction Monitoring Dataset
Keywords: condition monitoring; övervakning av skick; bearings; friction; machine learning; SCADA data; SCADA data; glycerol lubrication; glycerolsmörjning; hydropower; vattenkraft; Kaplan turbine; Kaplanturbin; anomaly detection; Avvikelsedetektering; predictive maintenance; prediktivt underhåll; Software Engineering; Programvaruteknik; Control Engineering; Reglerteknik; Other Mechanical Engineering; Annan maskinteknik